Tillage systems and seeding densities in sweet potato: quality of soil and reserve roots. - Pérez-Darniz, Maiby (2016)
The aim of this work was to determine the effect of tillage systems and seeding densities in sweet potato (Ipomoea batata (L) Lamb.). The study was held on the Central University of Venezuela, in the year of 2014. The degrees of severity of soil degradation and its correspondence with the scales of preference based on unit weight and dimensions of the tuberous root were determined. An arrangement of slots was used, where the tillage systems (TS) were assigned to the parcels and the seeding densities (SD) were assigned to slots. The TS consisted on vertical farming with a chisel (LC), with disc plowing (LA), conventional with three passes of the disc harrow (LCo) and a minimum with a pass of disc harrow (LM). The Ds were of 0,25 cm (D1) and 0,15 cm (D2) in the line. The physical quality of the soil was superior in the LA treatments. In these, the combination with the longest planting distances (LA-D1) favored the highest postharvest quality. On the contrary, the chisel treatments promoted the least acceptances among consumers. The light to moderate severity of soil degradation did not explain the postharvest quality variation. It is inferred on the lower rate in water movement in LD, that promoted and excess in humidity and a lower quality in the tuberous root.